Role and species–specific expression of colon T cell homing receptor GPR15 in colitis - Nguyen, Linh P. (Nat Immunol, 2014)
Lymphocyte recruitment maintains intestinal immune homeostasis but also contributes to inflammation. The orphan chemoattractant receptor GPR15 mediates regulatory T cell homing and immunosuppression in the mouse colon. We show that GPR15 is also expressed by mouse T(H)17 and T(H)1 effector cells, and is required for colitis in a model that depends on their trafficking to the colon. In humans GPR15 is expressed by effector cells including pathogenic T(H)2 cells in ulcerative colitis, but is not expressed by regulatory T (T(reg)) cells. The T(H)2 transcriptional activator GATA-3 and the T(reg)–associated transcriptional repressor FOXP3 robustly bind human, but not mouse, GPR15 enhancer sequences, correlating with expression. Our results highlight species differences in GPR15 regulation, and suggest it as a potential therapeutic target for colitis.